Briefly about scientific heritage of M. Kravchuk, Member of the Academy of Sciences of Ukraine - Parasyuk О. S.; Virchenko, N. O. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The article presents a brief survey of the principal stages in the life and scientific activity of the outstanding Ukrainian mathematician, M. Kravchuk, Academician of the Ukrainian Academy of Sciences, a victim of the purges in 1938, whose work was unjustly forgotten for many decades.